THE POLICY OF THE RUSSIAN EMPIRE IN THE TURKESTAN REGION IN THE SECOND HALF OF THE 19TH AND EARLY 20TH CENTURIES: MAIN DIRECTIONS AND OUTCOMES (Symposium on Natural and Applied Sciences, 2026)
In the second half of the 19th and early 20th centuries, the Turkestan Region occupied an important place in the foreign and domestic policy of the Russian Empire. As a result of military campaigns, Russia established control over a significant part of Central Asia and developed a system of administrative governance, with the Turkestan Governor-Generalship becoming its most important component. The policy of the Russian Empire in the region was simultaneously aimed at strengthening its military and political positions, developing the local economy, and integrating the region into the imperial administrative and economic system. At the same time, Anglo-Russian rivalry in Central Asia, known as the “Great Game,” played an important role in shaping Russian policy.